CARBONATE REEF OF THE KLAPANUNGGAL FORMATION IN THE BOGOR TROUGH, WEST JAVA - Abdurrokhim, . (Faculty of Geological Engineering, Universitas Padjadjaran, 2017)
AbstractThe Late Miocene shelf-margin carbonate reef is well exposed in the study area, and named as Klapanunggal Formation. The formation is characterized mainly by thick and massive reefal limestone with large foraminifers and other types of shell fragments, such as mollusks and echinoderms, and it have been developed in a response to the decrease in sediment discharge superimposed by relative rise in sea level during the late Miocene. Keyword: carbonate, Klapanunggal Formation, rimmed reef, shelf margin, Bogor Trough